QUANTITATIVE ESTIMATION AND ANTIMICROBIAL POTENTIAL OF ETHANOL EXTRACT OF DURIO ZIBETHINUS MURR. LEAVES - Chigurupati, Sridevi; Mohammad, Jahidul Islam; Vijayabalan, Shantini; Vaipuri, Narmatha Devi; Selvarajan, Kesavanarayanan Krishnan; Nemala, Appala Raju (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Current research is aimed to investigate the natural antimicrobial potential of Durio zibethinus murr. ethanol leaves extract (DZL). Methods: DZL was subjected to the preliminary phytochemical screening along with quantitative analysis of phenols and flavonoids. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were recorded. The agar well diffusion method was used to measure the antibacterial activity against gram positive and gram negative bacteria. The microorganisms used for the study were the ATCC strains of Bacillus subtilis, Enterococcus faecalis, Staphylococcus aureus, Streptococcus pyogenes, Neisseria gonorrhoeae, Pseudomonas aeruginosa and Escherichia coli. Results: DZL exhibited the highest MIC of 0.1mg/mL and MBC of 0.25 mg/mL against gram negative bacteria, Pseudomonas aeruginosa and Escherichia coli. At MIC of 0.1mg/mL, DZL displayed significant zone of inhibition against Pseudomonas aeruginosa and Escherichia coli compared to gentamycin. Conclusion: This research has shown that DZL has natural antibacterial properties against gram negative human pathogens.